Competencies for respectful maternity care: Identifying those most important to midwives worldwide. Issue 4 (12th February 2020) - Butler, Michelle M.; Fullerton, Judith; Aman, Cheryl
Abstract: Background: A respectful, person‐centered philosophy of maternity care has been emerging over several decades. Research conducted on behalf of the International Confederation of Midwives (ICM) to identify essential competencies for midwifery practice also identified the knowledge, skills, and professional behaviors that should be hallmarks of respectful maternity care practices among the global community of midwives. Methods: A three‐round, online, modified Delphi survey was conducted between April 2016 and October 2016. A total of 895 individuals from 90 of the then‐current 105 ICM member countries participated, with good representation across English, French, and Spanish speakers, high‐income, medium‐income, and low‐income countries, and educators and clinicians. Results: A total of 115 respectful maternity care (RMC)‐related items were endorsed by participants in Round 1 or 2. These items received average scores of between 90.24% and 99.10%, well above the 85% threshold required to be identified as within the scope of global midwifery practice. These items were compared with the 12 domains of RMC identified by Shakibazadeh and colleagues that defined respectful care during childbirth in health facilities globally, and with similar RMC frameworks, and were found to be highly congruent, thus demonstrating the high value of RMC within the core of midwifery practice. Discussion: ICM survey items were endorsed across all 12 RMC domains proposed by Shakibazadeh et al, and the findings affirmed that across ICM countries and regions, the philosophy of RMC was integrally related to the knowledge, skills, and professional behaviors that emerged as essential for basic midwifery practice.